Implantation of a subcutaneous implantable cardioverter defibrillator with right parasternal electrode position in a patient with D-transposition of the great arteries and concomitant AAI pacemaker: a case report. Issue 3 (12th September 2018) - Lüker, Jakob; Sultan, Arian; Sreeram, Narayanswami; Brockmeier, Konrad; Steven, Daniel
Abstract: Background: Implantable cardioverter defibrillator (ICD) therapy is indicated in patients with structural heart disease who have had an aborted cardiac arrest (ACA). After atrial repair of d-transposition of the great arteries (d-TGA, Mustard repair) patients seem to be at a higher risk of failing intraoperative subcutaneous ICD (S-ICD) shock testing. Case summary: We report the case of a 45-year-old patient with congenital heart disease (CHD) who suffered a cardiac arrest from ventricular fibrillation and was subsequently implanted with a S-ICD. We describe the challenges of ICD therapy in patients after Mustard procedure for d-TGA, with the additional challenge of concomitant AAI pacemaker therapy. In this patient, we opted for the implantation of an S-ICD, and detail the necessary considerations and operative technique employed in this patient. A right parasternal electrode position was chosen and intraoperative shock testing was successful. Discussion: Patients after atrial switch surgery for d-TGA and ACA require careful consideration of the appropriate type of ICD therapy. Subcutaneous ICD implantation with right parasternal electrode position may be a viable option in these patients.